2016
DOI: 10.17159/2078-516x/2016/v28i1a1415
|View full text |Cite
|
Sign up to set email alerts
|

An elite runner with cerebral palsy: cost of running determines athletic performance

Abstract: Background: Running performance is widely understood in terms of the Joyner model (VO 2max, %VO2max at ventilatory threshold (VT), running economy (often measured as cost of running (CR) as VO 2 in ml.kg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
1
1
Order By: Relevance
“…This difference is considerably lower than other studies found when comparing untrained age-matched controls with and without CP and highlights the positive effects of exercise 30. In addition, exercise efficiency is reduced in athletes with CP arguably due to muscle spasticity, decreased range of motion and pain 31 32. Anecdotally, higher BLa values at a given speed/power output have been reported in athletes with CP compared with able-bodied counterparts, which is likely related to the muscle spasticity negatively influencing the diffusion of blood from active muscle mass to venous blood.…”
Section: Impairment-related Considerationscontrasting
confidence: 56%
See 1 more Smart Citation
“…This difference is considerably lower than other studies found when comparing untrained age-matched controls with and without CP and highlights the positive effects of exercise 30. In addition, exercise efficiency is reduced in athletes with CP arguably due to muscle spasticity, decreased range of motion and pain 31 32. Anecdotally, higher BLa values at a given speed/power output have been reported in athletes with CP compared with able-bodied counterparts, which is likely related to the muscle spasticity negatively influencing the diffusion of blood from active muscle mass to venous blood.…”
Section: Impairment-related Considerationscontrasting
confidence: 56%
“… 30 In addition, exercise efficiency is reduced in athletes with CP arguably due to muscle spasticity, decreased range of motion and pain. 31 32 Anecdotally, higher BLa values at a given speed/power output have been reported in athletes with CP compared with able-bodied counterparts, which is likely related to the muscle spasticity negatively influencing the diffusion of blood from active muscle mass to venous blood. Furthermore, strength is reduced in athletes with CP due to decreased central input caused by brain damage, coactivation of antagonists muscles, increased type 1 muscle fibres, increased intramuscular fat and muscle atrophy.…”
Section: Impairment-related Considerationsmentioning
confidence: 99%